Religious Values in the Diwan of Imam Syafi'i: A Semiotic Analysis by Charles Sanders Pierce - Muhamad Naufal Rizky; Muhammad Haritsah Rais; M. Rosyid Ridho (Gunung Djati Conference Series, 2026)
This research focuses on analyzing the semiotic meaning of Charles Sanders Peirce which includes icons, indexes, and symbols constructed in the religious values of Diwan Imam Syafi'i. This study used a descriptive qualitative method. The object of research is several verses in Syarah Diwan Imam Syafi'i containing religious values related to aqidah, sharia, and morals. The results of the study concluded: The religious values found in Diwan Imam Syafi'i are represented through three main aspects, namely (1) Surrendering to Allah which reflects the value of faith in destiny and tawakkal, (2) Knowledge as the Light of Allah which emphasizes the importance of maintaining oneself from sin so that knowledge can be accepted properly, and (3) Noble Moral Behavior which includes qana'ah (contentment), humility, sincerity, and honesty. The meanings of icons, indexes, and symbols in the verses clearly show the relationship between literary expressions and spiritual teachings in Islam. The myths in Diwan Imam Syafi'i are depicted as symbols related to spiritual learning used in various verses.